First Molecular Evidence of Babesia vogeli, Babesia vulpes, and Theileria ovis in Dogs from Kyrgyzstan - Altay, Kursat; Erol, Ufuk; Sahin, Omer Faruk; Aydin, Mehmet Fatih; Aytmirzakizi, Ayperi; Dumanli, Nazir (Mdpi, 2023)
Tick-borne parasitic diseases cause mild to severe infections among vertebrate hosts, including dogs. Species in the genus Babesia are important tick-borne pathogens and have worldwide distributions. Although there are data on the prevalence and distribution of Babesia species among dogs around the world, there is no information available in Kyrgyzstan, according to a literature review. In this study, 337 dogs were screened by nested PCR for the presence of the 18S small subunit ribosomal RNA (18S SSU rRNA) gene of piroplasm species. Overall prevalence was 6.23% (21/337) for Babesia/Theileria spp. DNA sequencing of positively tested samples revealed that eighteen samples were infected with Babesia vogeli (B. vogeli) (5.34%), two samples with B. vulpes (0.59%), and one sample with Theileria ovis (T. ovis) (0.29%). The phylogenetic analyses and nucleotide sequences in contrast with those present in GenBank revealed that two nucleotide substitutions (594th and 627th) were found between B. vogeli isolates, including ours, indicating that the mutation is relatively rare. The sequences of other pathogens obtained in this study confirmed 100% nucleotide identity with B. vulpes and T. ovis sequences in GenBank. To the best of our knowledge, B. vogeli, B. vulpes, and T. ovis were detected for the first time in dogs from Kyrgyzstan, and it is thought that results will contribute to the understanding of the epidemiology of canine tick-borne pathogens in the country.
Keywords: B. vogeli; B. vulpes; PCR; DNA sequence; dog; Kyrgyzstan